Preliminary Application of a Quantitative Collateral Assessment Method in Acute Ischemic Stroke Patients With Endovascular Treatments: A Single-Center Study - Cao, Ruoyao; Qi, Peng; Jiang, Yun; Hu, Shen; Ye, Gengfan; Zhu, Yaxin; Li, Ling; You, Zilong; Chen, Juan (Frontiers in Neurology, 2021)
Objectives: To develop an efficient and quantitative assessment of collateral circulation on time maximum intensity projection CT angiography (tMIP CTA) in patients with acute ischemic stroke (AIS). Methods: Eighty-one AIS patients who underwent one-stop CTA-CT perfusion (CTP) from February 2016 to October 2020 were retrospectively reviewed. Single-phase CTA (sCTA) and tMIP CTA were developed from CTP data. Ischemic core (IC) volume, ischemic penumbra volume and mismatch ratio were calculated. The Tan scale was used for qualitative evaluation of collaterals based on sCTA and tMIP CTA. Quantitative collateral circulation (CCq) parameters were calculated semi-automatically with software by the ratio of the vascular volume (V) on both hemispheres, including tMIP CTA VCCq and sCTA VCCq. Spearman correlation analysis was used to analyze the correlation of collateral-related parameters with final infarct volume (FIV). ROC and multivariable regression analysis were calculated to compare the significance of the above parameters in clinical outcome evaluation. The analysis time of the observers was also compared. Results: tMIP CTA VCCq (r = 0.61, p < 0.01), IC volume (r = 0.66, p < 0.01), Tan score on tMIP CTA (r = 0.52, p < 0.01) and mismatch ratio (r = 0.60, p < 0.01) showed moderate negative correlations with FIV. tMIP CTA VCCq showed the best prognostic value for clinical outcome (AUC = 0.93, p < 0.001), and was an independent predictive factor of clinical outcome (OR = 0.14, p = 0.009). There was no difference in analysis time of tMIP CTA VCCq among observers (p = 0.079). Conclusion: The quantitative evaluation of collateral circulation on tMIP CTA is associated with clinical outcomes in AIS patients with endovascular treatments.